Methodological Aspects of Intensifying Management of Enterprise Economic Behavior in the Context of Neo-Industrial Modernization - Protsenko Valentyna M. (Problemi Ekonomiki, 2020)
The aim of the article is to form methodological aspects of intensifying economic behavior management in the context of neo-industrial modernization. The work notes that the sequence and success of market transformations is largely determined by economic behavior of enterprises, their adaptation to new requirements of modern reality. One of the main reasons for the inability of Ukrainian industrial enterprises to overcome the crisis is their unpreparedness to modernize production and increase the output of competitive products. The elimination of these causes requires that enterprises have a certain strategy and tactics of economic behavior. The intensification of management of enterprise economic behavior in the context of neo-industrial modernization as a phenomenon is the subject of study of both economic science and sociology. It is determined that the problem of intensifying management of enterprise economic behavior in the context of neo-industrial modernization can be methodologically overcome. This is possible in the case of bringing up the issue of its absolutist and relativistic assessment, stating that rationality as a fundamental characteristic of economic behavior is a civilized value, has both methodological and axiological orientation. The article highlights the main directions of research on the intensification of management of enterprise economic behavior in the context of neo-industrial modernization, and proposes a methodology for intensifying economic behavior management in the context of neo-industrial modernization.